Long-term clinical outcome of gastric MALT lymphoma after eradication of Helicobacter pylori: a multicentre cohort follow-up study of 420 patients in Japan. Issue 4 (2nd September 2011) - Nakamura, Shotaro; Sugiyama, Toshiro; Matsumoto, Takayuki; Iijima, Katsunori; Ono, Shouko; Tajika, Masahiro; Tari, Akira; Kitadai, Yasuhiko; Matsumoto, Hiroshi; Nagaya, Tadanobu; Kamoshida, Toshiro; Watanabe, Norihiko; et al.
Abstract : Objective: A multicentre cohort follow-up study of a large number of patients with gastric mucosa-associated lymphoid tissue (MALT) lymphoma was conducted to elucidate the long-term outcome of the disease after Helicobacter pylori eradication. Methods: 420 patients with gastric low-grade MALT lymphoma who had undergone successful H pylori eradication and been followed up for at least 3 years were registered from 21 participating institutes. Responders to treatment were defined as patients whose post-treatment biopsies showed complete histological response (ChR) or probable minimal residual disease (pMRD). Treatment failure was defined as the status of progressive disease or lymphoma relapse after ChR/pMRD. Results: 323 patients (77%) responded to H pylori eradication. A logistic regression analysis showed that absence of H pylori, submucosal invasion determined by endoscopic ultrasonography and t(11;18)/ API2-MALT1 were independent predictors of resistance to H pylori eradication. During the follow-up periods ranging from 3.0 to 14.6 years (mean 6.5 years, median 6.04 years), the disease relapsed in 10 of 323 responders (3.1%) while progressive disease was found in 27 of 97 non-responders (27%). Thus, 37 of 420 patients (8.8%) were regarded as treatment failures. Of these 37 patients, transformation into diffuse large B cell lymphoma occurred in nine patients. Among the non-responders and relapsed patients, 17 patients were subjected to a 'watch and wait' strategy while 90 patients underwent second-line treatments including radiotherapy (n=49), chemotherapy (n=26), surgical resection (n=6), chemoradiotherapy (n=5), antibiotic treatment (n=2), rituximab monotherapy (n=1) or endoscopic resection (n=1). Probabilities of freedom from treatment failure, overall survival and event-free survival after 10 years were 90%, 95% and 86%, respectively. Cox multivariate analysis revealed endoscopic non-superficial type to be an independent prognostic factor for adverse freedom from treatment failure, overall survival and event-free survival. Conclusions: The excellent long-term outcome of gastric MALT lymphoma after H pylori eradication was confirmed by this large-scale follow-up study.